PTU-041 Colonoscopic perforations in the english nhs bowel cancer screening programme (nhsbcsp). (22nd June 2015) - Derbyshire, E; Nickerson, C; Hungin, A; Rutter, MD
Abstract : Introduction: Colonoscopic perforation remains one of the most serious adverse events associated with colonoscopy. Colonoscopies in the English NHSBCSP are performed at 61 Screening Centres. There is a robust system for capturing the details of adverse events; patients are contacted at 24 h and 30 days post procedure, Centres complete an adverse event form, reviewed by regional Quality Assurance leads, and event details are entered onto a national web based database, the Bowel Cancer Screening System (BCSS). We have previously reported an NHSBCSP perforation rate of 0.06%, and risk factors for perforation. 1 This study aimed to (1) describe perforation presentation, management and outcomes, and (2) determine perforation morbidity and mortality rates. Method: We identified all reported colonoscopic perforations from the start of the NHSBCSP in 2006 up to 13/03/2014. The NHSBCSP defines perforation as: air, luminal contents or instrumentation outside the gastrointestinal tract. BCSS was interrogated to identify patient and procedure details. Centres completed a detailed online questionnaire on presentation, management and outcome. Results: Of 147 perforations identified, complete data on 117 was recieved. 58.1% were male, mean age was 65.5. 69.2% were therapeutic perforations. The endoscopist visualised the perforation in 12.8% of cases (median perforation size 5 mm) applying endoclips in 80% of these. 54.5% of diagnostic perforations were in the sigmoid colon. Of 115 patients admitted to hospital, 31.3% were admitted immediately following colonoscopy, 67% represented with abdominal pain having been discharged, 1.7% were recalled following radiological investigation. 54.8% had surgery including 86.4% of diagnostic and 45.7% of therapeutic perforations. 26.1% (47.6% of those who had surgery) were left with a stoma. Post Perforation Morbidity defined as an in-patient complication or new diagnosis was 19.7%. Median hospital stay was 9.5 days (range 0–51 days). 25.2% were admitted to the Intensive Care Unit. The mortality rate was 0.87%. Conclusion: This is the largest case series reporting outcomes after colonoscopic perforation in the UK. The colonoscopist recognised the perforation during colonoscopy in only 12.8% of cases, the majority representing with abdominal pain after a mean of 2 days. 44.3% of perforations admitted were successfully managed conseravtively including 13.6% of diagnostic and 53.1% of therapeutic perforations. Over a quarter of perforations admitted are likely to leave hospital with a stoma. A post perforation morbidity rate of 19.7% and mortality rate of 0.87% compares favourably with other series. Disclosure of interest: None Declared. Reference: Rutter MD, et al . Endoscopy 2014:90–97